The chloroplast genome of black pepper (Piper nigrum L.) and its comparative analysis with related Piper species - Gaikwad, Ambika Baldev; Kaila, Tanvi; Maurya, Avantika; Kumari, Ratna; Rangan, Parimalan; Wankhede, Dhammaprakash Pandhari; Bhat, K. V. (Frontiers in Plant Science, 2023)
Piper nigrum also known as black pepper is an economically and ecologically important crop of the genus Piper. It has been titled as the king of spices due to its wide consumption throughout the world. In the present investigation, the chloroplast genome of P. nigrum has been assembled from the whole genome sequence by integrating the short and long reads generated through Illumina and PacBio platforms respectively. The plastid genome was observed to be 161,522bp in size, having quadripartite structure with a large single copy (LSC) region of 89,153bp and a small single copy (SSC) region of 18,255bp separated by a copy of inverted repeats (IRs), each 27,057bp in length. Taking into consideration all the duplicated genes, a total of 131 genes were observed, which included 81 protein coding genes, 37 tRNAs, 4 rRNAs and 1 pseudogene. Individually, LSC region consisted of 83 genes, SSC region had 13 genes and 18 genes were present in each IR region. Additionally, 216 SSRs were also detected. The features of the plastid genome were compared to the previously reported plastid genomes of the genus Piper. Our results provide useful insights into evolutionary and molecular studies of black pepper which will contribute to its further genetic improvement and breeding.